Suppression of MCP-1, IFN-γ and IL-6 production of HNSCC ex vivo by pembrolizumab added to docetaxel and cisplatin (TP) exceeding those of TP alone is linked to improved survival - Jana Wellhausen; Louisa Röhl; Michael Berszin; Irene Krücken; Irene Krücken; Veit Zebralla; Veit Zebralla; Markus Pirlich; Markus Pirlich; Matthaeus Stoehr; Matthaeus Stoehr; Susanne Wiegand; et al. (Frontiers in Immunology)
BackgroundAdding pembrolizumab, an anti-PD-1 antibody approved for treatment of head and neck squamous cell carcinoma (HNSCC) to neoadjuvant (induction-) chemotherapy utilizing docetaxel and cisplatin (TP) followed by radiotherapy may improve outcome in larynx organ-preservation (LOP) that is investigated in the European Larynx-Organ preservation Study (ELOS). As biomarkers for response to TP and pembrolizumab +TP are missing but may include cytokines, this work aims on determining cytokines potentially linked to outcome as prognostic markers sufficient to predict and/or monitor response to successful LOP.MethodsCollagenase IV digests were generated from 47 histopathological confirmed HNSCC tumor samples and seeded in 96-well plates containing pembrolizumab, docetaxel, cisplatin either solely or in binary or ternary combination. According to the FLAVINO protocol, supernatants were collected after 3 days, adherent cells fixed using ethanol, air-dried and pan-cytokeratin positive epithelial cells counted using fluorescence microscopy. The cytokines IL-6, IL-8, IFN-γ, IP-10, MCP-1, TNF-α, and VEGF in the supernatant were quantified by sandwich ELISA.ResultsThe mode of interaction between pembrolizumab and TP was assessed and correlated to outcome (overall, disease-specific and progression-free survival of patients). Suppression of MCP-1, IFN-γ and IL-6 production by pembrolizumab + TP exceeding the suppressive effect of TP was detected in the majority of samples and linked to improved survival. Multivariate Cox proportional hazard regression modeling revealed MCP-1, IFN-γ and IL-6 as independent outcome predictors.ConclusionsComparing response to TP vs. pembrolizumab vs. TP + pembrolizumab may allow for identification of patients with superior outcome independent from treatment applied.